THE IMPACT OF LABORATORY AND NURSING INTERACTION ON DIAGNOSTIC ACCURACY AND TIMELINESS OF MEDICAL DECISION-MAKING - Norah Oudah Almunaffi Alruwaili, Jamilah Shehab Silan Alruwaili, Fatimah Hamad Nasser Alwaliai, Musaddaha Asri Mater Alhazmi, Rahaf Saleh Mohammad Alshammari, Khulfaha Ali Salem Alenazy (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Effective interaction between laboratory services and nursing teams plays a crucial role in ensuring accurate and timely diagnostic results, which directly influence medical decision-making. Delays in sample collection, labeling errors, communication gaps, and improper specimen handling can compromise diagnostic accuracy and extend turnaround times. This literature-based paper explores how collaboration, communication quality, standardized procedures, and professional competency between nursing and laboratory staff affect diagnostic processes. Evidence from peer-reviewed studies shows that strong interprofessional coordination enhances test accuracy, reduces errors, and speeds up clinical interventions, ultimately improving patient outcomes. Strengthening the relationship between laboratory and nursing teams is therefore essential for supporting safe, efficient, and reliable healthcare services.